2021
DOI: 10.1016/j.intimp.2021.107732
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of IVIG (intravenous immunoglobulin) for corona virus disease 2019 (COVID-19): A meta-analysis

Abstract: Background The benefit of IVIG (Intravenous Immunoglobulin) therapy for COVID-19 remains controversial. We performed a meta-analysis to investigate the efficacy of IVIG treatment in patients with COVID-19. Methods We searched articles from Web of Science, PubMed, Embase, the Cochrane Library, MedRxiv between 1 January 2020 and February 17, 2021. We selected randomized clinical trials and observational studies with a control group to assess the efficiency of IVIG in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…Given that COVID-19 largely resembles an autoimmune disorder in the late stages, IVIGs are presumed to act as an immune modulator by dampening the excessive immune response to SARS-CoV-2 which drives pathology [33,34]. A systematic review and metaanalysis by Xiang and colleagues on three clinical trials and three cohort studies [12] found that the effect of IVIG was associated with the severity of COVID-19, as it was highest in the critical subgroup. Our updated systematic review, performed on a higher number of studies and including more patients, gave different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that COVID-19 largely resembles an autoimmune disorder in the late stages, IVIGs are presumed to act as an immune modulator by dampening the excessive immune response to SARS-CoV-2 which drives pathology [33,34]. A systematic review and metaanalysis by Xiang and colleagues on three clinical trials and three cohort studies [12] found that the effect of IVIG was associated with the severity of COVID-19, as it was highest in the critical subgroup. Our updated systematic review, performed on a higher number of studies and including more patients, gave different results.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various therapeutic and prophylactic strategies developed to contain the COVID-19 epidemic, passive immunization by COVID-19 convalescent plasma (CCP) transfusion has been proven effective when CCP was administered early (within 72 h from symptom onset) and with a high titer ( >1:160) of anti-SARS-CoV-2 neutralizing antibodies (nAb) [6,7]. Late disease stages are characterized by an exaggerated immune response, which responds to immunosuppressants: high-dose intravenous immunoglobulin (IVIG), based on previous positive experiences in autoimmune, inflammatory and other infectious diseases, including coronavirus-induced infections [8,9], has been also proposed for COVID-19 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors could have confounded the results of the study. A recent meta-analysis of 4 clinical trials and 3 cohort studies including 825 hospitalized patients showed that IVIG use was associated with a significant reduction in mortality in the critical subgroup of Covid 19 patients, but not in the non-severe subgroups [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that using IVIG could reduce the mortality rate, risk of disease progression, and increase survival in critical subgroups of COVID-19 patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%